A novel deleterious ETFA promoter variant causative of multiple acyl‐CoA dehydrogenase deficiency. Issue 4 (28th December 2022) - Prasun, Pankaj; Evans, Anthony; Cork, Emalyn; Houten, Sander M.; Webb, Bryn D.
Abstract: Multiple acyl‐CoA dehydrogenase deficiency (MADD) is an autosomal recessive disorder of fatty acid, amino acid, and choline metabolism. We describe a patient identified through newborn screening in which the diagnosis of MADD was confirmed based on metabolic profiling, but clinical molecular sequencing of ETFA, ETFB, and ETFDH was normal. In order to identify the genetic etiology of MADD, we performed whole genome sequencing and identified a novel homozygous promoter variant in ETFA (c.‐85G > A). Subsequent studies showed decreased ETFA protein expression in lymphoblasts. A promoter luciferase assay confirmed decreased activity of the mutant promoter. In both assays, the variant displayed considerable residual activity, therefore we speculate that our patient may have a late onset form of MADD (Type III). Our findings may be helpful in establishing a molecular diagnosis in other MADD patients with a characteristic biochemical profile but apparently normal molecular studies.